2011
DOI: 10.1111/j.2044-8325.2011.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Resources and time pressure as day‐level antecedents of work engagement

Abstract: This diary study adds to research on the Job Demands-Resources model. We test main propositions of this model on the level of daily processes, namely, additive and interaction effects of day-specific job demands and day-specific job and personal resources on dayspecific work engagement. One hundred and fourteen employees completed electronic questionnaires three times a day over the course of one working week. Hierarchical linear models indicated that day-specific resources (psychological climate, job control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(150 citation statements)
references
References 38 publications
12
137
0
1
Order By: Relevance
“…Recent research has also shown how levels of work engagement can fluctuate on a weekly or daily basis, depending on experiences during the day (Breevaart, Bakker, Demerouti, & Hetland, 2012;Kühnel, Sonnentag, & Bledow, 2012;Sonnentag, Mojza, Demerouti, & Bakker, 2012). These results underline the understanding of engagement as experiences at work that are relatively stable, but will fluctuate based on daily changes.…”
Section: Passion and Work Engagementmentioning
confidence: 91%
“…Recent research has also shown how levels of work engagement can fluctuate on a weekly or daily basis, depending on experiences during the day (Breevaart, Bakker, Demerouti, & Hetland, 2012;Kühnel, Sonnentag, & Bledow, 2012;Sonnentag, Mojza, Demerouti, & Bakker, 2012). These results underline the understanding of engagement as experiences at work that are relatively stable, but will fluctuate based on daily changes.…”
Section: Passion and Work Engagementmentioning
confidence: 91%
“…Prior research also states that job resources are particularly important when worker faces high job demands (e.g. Kühnel et al, 2012).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Prior to testing the hypothesis a confirmatory factor analysis using Mplus 6.12 (Muthén & Muthén, 1998-2012 was performed to validate the job demands, job control and social support measurements. Given the big sample size, instead of chi-square test the goodness of model was examined using other fit indices: CFI and TLI (> .95 indicates a good fit), RMSEA (< .06 indicates a good fit) and SRMR (< .08 indicates a good fit) (e.g., Brown, 2006;Hu & Bentler, 1999).…”
Section: Validation Of Measurementsmentioning
confidence: 99%
“…62 Recent diary studies 184,262,266 that have examined the fluctuations of engagement levels through the working day suggest that engagement is a state that is susceptible to variation depending on environmental factors. It has additionally been proposed that engagement may be directed towards individual work tasks or be conceived as a collective, team-level experience.…”
Section: Synthesising the Evidence On Definitions Of Engagementmentioning
confidence: 99%